Future-Proofing Islamic Education Management in the Era of Artificial Intelligence: A Literature Review on Adaptation and the Existence of Science - Achmad Nashrul Wahib; Ardiyansyah, Ardiyansyah; Ahmad Rahman Budiman; Mokhammad Zainuri; Syamsul Anam; Mirdawati; Maulidyah Fitriah (Edumaspul: Jurnal Pendidikan, 2026)
The development of Artificial Intelligence (AI) has transformed the global educational landscape and driven the emergence of a new paradigm in educational governance. Amid this transformation, Islamic Education Management (IEM) faces challenges related not only to institutional digitalization but also to the sustainability, relevance, and future existence of its science. To date, most research has focused on the use of AI in learning and the digital transformation of educational institutions, while studies specifically addressing the sustainability strategy for IEM in the AI ​​era are still limited. This study aims to analyze strategies for adapting and strengthening the scientific existence of Islamic Education Management through a future-proofing perspective as a new paradigm for scientific sustainability. The study used a qualitative approach with a literature review design (library research) sourced from reputable scientific articles, academic books, and international and national policy documents published in the 2020–2026 period. Data were analyzed through content analysis, thematic analysis, and narrative synthesis. The results indicate that Islamic Education Management requires a paradigm shift from an administrative approach to an adaptive, strategic, and future-oriented scientific system. AI is not positioned as a substitute for Islamic values, but rather as an accelerator that strengthens educational governance and decision-making capacity. This study also identifies five future competencies: digital leadership, AI literacy, data-driven decision-making, adaptive governance, and ethical Islamic governance. Furthermore, this study produces a conceptual model of the Future-Proofing Islamic Educational Management Framework (FPIEM), which integrates scientific adaptation, adaptive governance, academic existence, and the social impact of Islamic education in a sustainable manner. The main contribution of this research lies in the introduction of the future-proofing paradigm as a new approach to strengthening the sustainability of Islamic Education Management in the era of Artificial Intelligence. Further research is recommended to empirically test this model in various Islamic educational institutions